Study of natural herbal dyes photodegradation effect to optical properties for dye-sensitized solar cells - Triyanto, Aripin; Nora’aini Ali; Hasiah Salleh; Setiawan, Jan; Norhafiza I. Yatim; Nurul Alfatihah Mohd Arifin; Nur Salihah Alias (Penerbit Universiti Kebangsaan Malaysia, 2024)
The stability of natural dyes for use in dye-sensitive solar cells is known from their photodegradation characteristics. Photodegradation effects using artificial light radiation on natural herbal dyes were investigated. Three natural herbal dyes, namely Fagraea acuminatissima, sappanwood, and kulit setong were used in this study. The stability of the natural herbal dyes under artificial light radiation was studied. The optical properties of the natural herbal dyes as indicators of their stability were characterized using FTIR and UV-VIS absorption. Stability testing of natural herbal dyes was conducted in a room with artificial lighting for 5 weeks. Observations of changes in their optical properties were performed weekly. It can be seen that all three natural herbal dyes contained anthocyanin. In addition to anthocyanin, acuminatissima and sappanwood also contain chlorophyll. In contrast, the kulit setong contains beta-carotene in addition to anthocyanin. The degradation percentage showed that sappanwood degrade to all of its pigments. While an increase occurred in the chlorophyll peak of acuminatissima and the beta-carotene peak of kulit setong. This clearly shows that acuminatissima has the highest stability, and potentially increases the efficiency of solar cells.